1986
DOI: 10.1111/j.1463-6409.1986.tb00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytotaxonomic study in the order Falconiformes (Aves)

Abstract: Cytotaxonomic study in the order Falconiformes (Aves).-Zool. Scr. IS: 351-356.Karyotypes of six species of birds of the order Falconiformes are presented. The chromosomes of three of these, Neophron percnopterus, Butastur teesa (family Accipitridae) and Falco chicquera (family Falconidae) are described for the first time. The systematic position of these birds are discussed in relation to the karyological characters of other diurnal birds of prey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Karyological evidence also supports the distinctness of Gypaetus from other vultures, but not that of Neophron: Aegypius, Torgos, Sarcogyps, Gyps and Necrosyrtes have identical karyotypes (2 = 66), from which Gypaetus differs considerably in the number of chromosomes ( 2n -60) and their morphology (DeBoer 1976;DeBoer & Sinoo 1984). In a different study, the karyotype of Neophron (2 n -66) was found to be similar to that of most Aegypiines (Ansari & Kaul 1986). The alternative hypothesis to polyphyly, i.e.…”
Section: {D) R E La Tio N Sh Ip S a M O N G O Ld W Orld V U Ltu R E Smentioning
confidence: 78%
“…Karyological evidence also supports the distinctness of Gypaetus from other vultures, but not that of Neophron: Aegypius, Torgos, Sarcogyps, Gyps and Necrosyrtes have identical karyotypes (2 = 66), from which Gypaetus differs considerably in the number of chromosomes ( 2n -60) and their morphology (DeBoer 1976;DeBoer & Sinoo 1984). In a different study, the karyotype of Neophron (2 n -66) was found to be similar to that of most Aegypiines (Ansari & Kaul 1986). The alternative hypothesis to polyphyly, i.e.…”
Section: {D) R E La Tio N Sh Ip S a M O N G O Ld W Orld V U Ltu R E Smentioning
confidence: 78%
“…as outgroups for the Falconidae ( Griffiths, 1994 , 1999 ; Haring et al , 2001 ; Griffiths et al , 2004 ), or in treatments of other phylogenetic issues within the Accipitridae ( Seibold & Helbig, 1996 ; Helbig et al , 2005 ; Lerner & Mindell, 2005 ). Cytotaxonomy appears to possess signal, especially in the comparatively intensively studied Falconiformes, but even phenetic groupings of cytotaxonomy have defied interpretation ( Ansari & Kaul, 1986 ). The recent sequence-based phylogeny proposed for the diurnal birds of prey ( Lerner & Mindell, 2005 ) emphasized species-level relationships within the Accipitridae, and Fain & Houde (2004 ) failed to resolve relationships among the diurnal raptors.…”
Section: B Irds Of Prey – Diurnal and Nomentioning
confidence: 99%